Positive Implicative Soju Ideals in BCK-Algebras - Xin, Xiao Long; Borzooei, Rajab Ali; Jun, Young Bae (Bulletin of the Section of Logic, 2019)
The notion of positive implicative soju ideal in BCK-algebra is introduced, and several properties are investigated. Relations between soju ideal and positive implicative soju ideal are considered, and characterizations of positive implicative soju ideal are established. Finally, extension property for positive implicative soju ideal is constructed.